2006
DOI: 10.1016/j.gexplo.2005.08.084
|View full text |Cite
|
Sign up to set email alerts
|

pH-Dependent iron oxide precipitation in a subterranean estuary

Abstract: Iron-oxide-coated sediment particles in subterranean estuaries can act as a geochemical barrier (biron curtainQ) for various chemical species in groundwater (e.g. phosphate), thus limiting their discharge to coastal waters. Little is known about the factors controlling this Fe-oxide precipitation. Here, we implement a simple reaction network in a 1D reactive transport model (RTM), to investigate the effect of O 2 and pH gradients along a flow-line in the subterranean estuary of Waquoit Bay (Cape Cod, Massachus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
81
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(90 citation statements)
references
References 10 publications
8
81
1
Order By: Relevance
“…These values are consistent with the extensive intrusion of seawater that can occur in karst aquifers and the large volume of fresh and saline water movement in such systems. The mixed brackish/saline water discharging in many coastal karst systems is chemically different than either the meteoric or surface seawater due to reactions in the subterranean estuary (Slomp and Van Cappellen, 2004;Spiteri et al, 2006) and should be explicitly determined as this water may have significant impact on coastal ecosystems (Moore, 2010). Young et al (2008) found that the Celestun Lagoon on the northwest corner of the Yucatan Peninsula had different groundwater sources, (1) a low salinity, low radium and high nitrate source, and (2) a brackish source with high radium and less nitrate.…”
Section: Sgd: Ojos and Beach Facementioning
confidence: 99%
“…These values are consistent with the extensive intrusion of seawater that can occur in karst aquifers and the large volume of fresh and saline water movement in such systems. The mixed brackish/saline water discharging in many coastal karst systems is chemically different than either the meteoric or surface seawater due to reactions in the subterranean estuary (Slomp and Van Cappellen, 2004;Spiteri et al, 2006) and should be explicitly determined as this water may have significant impact on coastal ecosystems (Moore, 2010). Young et al (2008) found that the Celestun Lagoon on the northwest corner of the Yucatan Peninsula had different groundwater sources, (1) a low salinity, low radium and high nitrate source, and (2) a brackish source with high radium and less nitrate.…”
Section: Sgd: Ojos and Beach Facementioning
confidence: 99%
“…The process controlling this removal is not obvious from the current dataset, although scavenging onto authigenic iron oxides may play a role (Andersson et al, 1994). Sorption by Fe-oxyhydroxides may be especially important in the STE, due to extensive 250 formation of such precipitates during mixing of meteoric and marine groundwaters (Charette et al, 2002;Charette et al, 2005;Spiteri et al, 2006). However, Sr removal from solution by this mechanism does not appear to be ubiquitous, given that Sr depletion was not evident at some sites where Fe precipitation has been clearly documented (e.g., Waquoit Bay and Great South Bay; Charette andSholkovitz, 2006, Beck et al, 2010).…”
Section: Sr In the Subterranean Estuary 240mentioning
confidence: 93%
“…They found a significant correlation between Fe and P in aquifer sediments, and suggested that the iron curtain could act as a natural permeable reactive barrier for in situ removal of chemical species such as phosphate (PO4-P) that have a strong affinity for Fe (hydr)oxides. Later, Spiteri et al [2006] used a reactive transport model to demonstrate that the iron curtain's formation is driven largely by pH (rather than redox) gradients, and that this process may be responsible for greatly reduced (PO4-P) transport to the coastal ocean via SGD.…”
Section: Metalsmentioning
confidence: 99%